PAI Study Program Strategy to Improve Students' Academic Achievement - Rizky indira Amalia Nasution; Arlina Arlina (At-Tarbiyat, 2023)
This article examines academic achievement, human resources and higher education benchmarks. This is very important for a student to know where his abilities are. This research uses qualitative methods to collect data by direct observation in the field and conducting interviews with students at the North Sumatra State Islamic University (UINSU) in the PAI Study Program as well as running a Documentation Study which is used to test, interpret and predict as a data source. The results of this research are about the strategies of the PAI study program in improving student academic achievement. Some of the strategies implemented are providing academic ethics at the beginning of lectures, encouraging students to read from various sources, establishing a scheduled learning system, establishing an effective lecture system, urging students to maintain a balance between studies, work and organizations; assess students' academic abilities; and conducting personal counselling and collaboration with families in helping students.